Probing distance and electrical potential within a protein pore with tethered DNA. - Howorka, S; Bayley, H (2002)
DNA molecules tethered inside a protein pore can be used as a tool to probe distance and electrical potential. The approach and its limitations were tested with alpha-hemolysin, a pore of known structure. A single oligonucleotide was attached to an engineered cysteine to allow the binding of complementary DNA strands inside the wide internal cavity of the extramembranous domain of the pore. The reversible binding of individual oligonucleotides produced transient current blockades in single channel current recordings. To probe the internal structure of the pore, oligonucleotides with 5' overhangs of deoxyadenosines and deoxythymidines up to nine bases in length were used. The characteristics of the blockades produced by the oligonucleotides indicated that single-stranded overhangs of increasing length first approach and then thread into the transmembrane beta-barrel. The distance from the point at which the DNA was attached and the internal entrance to the barrel is 43 A, consistent with the lengths of the DNA probes and the signals produced by them. In addition, the tethered DNAs were used to probe the electrical potential within the protein pore. Binding events of oligonucleotides with an overhang of five bases or more, which threaded into the beta-barrel, exhibited shorter residence times at higher applied potentials. This finding is consistent with the idea that the main potential drop is across the alpha-hemolysin transmembrane beta-barrel, rather than the entire length of the lumen of the pore. It therefore explains why the kinetics and thermodynamics of formation of short duplexes within the extramembranous cavity of the pore are similar to those measured in solution, and bolsters the idea that a "DNA nanopore" provides a useful means for examining duplex formation at the single molecule level.